Antibody response against 26 and 46 kilodalton released proteins of yersinia in yersinia triggered reactive arthritis. Issue 11 (November 1992) - Mäki-Ikola, O; Pulz, M; Heesemann, J; Lahesmaa, R; Saario, R; Toivanen, A; Granfors, K
Abstract : Using an inhibition enzyme linked immunosorbent assay (ELISA) the serum antibody responses against released proteins of yersinia of molecular weights 26 and 46 kilodaltons were studied in 37 patients with and in 21 patients without reactive arthritis following yersinia infection. Although no difference was seen for the 46 kilodalton released protein, patients with yersinia triggered reactive arthritis had higher levels of antibodies against the 26 kilodalton released protein at the beginning of the disease than patients with uncomplicated yersiniosis. This may indicate an increased production of this protein in the early infection leading to poorer phagocytosis of the bacteria and thereby to the persistence of yersinia organisms within the arthritic host.